Income or leisure? On the hidden benefits of (un-)employment - Adrian Chadi; Clemens Hetschko (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2017)
We study the usually assumed trade-off between income and leisure in labor supply decisions using comprehensive German panel data. We compare non-employed individuals after plant closures with employed people regarding both income and time use as well as their subjective perceptions of these two factors. We find that the gain of non-working time translates into higher satisfaction with free time, while time spent on hobbies increases to a lesser extent than home production. Additionally, satisfaction with family life increases, which may be a hidden benefit of being unemployed. In contrast, satisfaction with income strongly declines when becoming jobless. Identity utility from earning a living may play the role of a hidden benefit of employment. Finally, we examine subjective assessments of income and leisure as potential predictors for job take-up. Non-employed people are particularly likely to take up a job soon when they are dissatisfied with their income.
Keywords: D01; D13; I31; J22; J64; J65; 330; labor supply; plant closure; leisure; work-family conflict; life satisfaction; income satisfaction; free time satisfaction; family satisfaction